Elective caesarean section on maternal request prior to 39 gestational weeks and childhood psychopathology: a birth cohort study in China - Kun Huang; Shuangqin Yan; Xiaoyan Wu; Peng Zhu; Fangbiao Tao (BMC Psychiatry, 2019)
Abstract Background The recommendation of non-indicated caesarean section (CS) after 39 gestational weeks has been announced based on evidence of maternal and infant physiological effects. The potential psychological risks have not been acknowledged. This study aims to investigate emotional and behavioral problems in pre-school children born with elective CS (ECS) on maternal request prior to 39 weeks. Methods Pregnant women within 12 gestational weeks between November 2008 and October 2010 were invited to participate in the China-Anhui Birth Cohort Study (C-ABCS). They were asked to complete a self-administered questionnaire respectively in 1st and 3rd trimester of pregnancy to collect basic maternal characteristics. Pregnant complications and delivery modes were abstracted from medical notes. Their singleton live births were followed up at preschool age. Strengths and Difficulties Questionnaires (SDQ) were completed by parents to assess children’s emotional and behavioral problems. A total of 3319 mother-child pairs were put into the final analysis. Descriptive analysis and binary logistic regression analysis were used to assess the impact of delivery modes on abnormalities in SDQ dimensions at various gestational ages. Results The prevalence of ECS on maternal request prior to 39 weeks, at 39–40 weeks, and after 41 weeks was 16.6, 23.7 and 15.9%, respectively. Compared with those born vaginally, children born with ECS on maternal request were more likely to have total difficult problems (RR 1.519, 95% confidence interval 1.077 to 2.142). ECS on maternal request was the independent predictor of emotional problems (3.479, 1.676 to 7.222) and total difficult problems (2.172, 1.175 to 4.016) in children born prior to 39 gestational weeks. Conclusion Children delivered by ECS on maternal request have an increased risk to have emotional and behavioral problems prior to 39 gestational weeks at preschool age. The potential psychological implication prior to 39 weeks has been added to the roster of impacts of ECS on maternal request. Further research is needed to probe the potential biological mechanisms.